2014
DOI: 10.1097/md.0000000000000204
|View full text |Cite|
|
Sign up to set email alerts
|

Prior to the Oral Therapy, What Do We Know About HCV-4 in Egypt

Abstract: Hepatitis C virus (HCV) affects over 180 million people worldwide and it's the leading cause of chronic liver diseases and hepatocellular carcinoma. HCV is classified into seven major genotypes and a series of subtypes. In general, HCV genotype 4 (HCV-4) is common in the Middle East and Africa, where it is responsible for more than 80% of HCV infections. Although HCV-4 is the cause of approximately 20% of the 180 million cases of chronic hepatitis C worldwide, it has not been a major subject of research yet. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“… 3 5 In Egypt, 15% of an estimated population of 85 million are HCV positive, of whom >90% are infected with genotype 4 (GT 4). 6 , 7 The rapid emergence of the epidemic in Egypt was initially fueled by the mass treatment of schistosomiasis using the injectable drug tartar emetic at some stage during the 1960s and 1970s. 8 …”
Section: Introductionmentioning
confidence: 99%
“… 3 5 In Egypt, 15% of an estimated population of 85 million are HCV positive, of whom >90% are infected with genotype 4 (GT 4). 6 , 7 The rapid emergence of the epidemic in Egypt was initially fueled by the mass treatment of schistosomiasis using the injectable drug tartar emetic at some stage during the 1960s and 1970s. 8 …”
Section: Introductionmentioning
confidence: 99%
“… 6 The bulk of the G4 disease burden resides in the Middle East, Northern Africa and Sub-Saharan Africa with the largest single G4 population (and arguably the best characterised cohort) residing in Egypt where 15% of an estimated population of 80 million are HCV positive, of which 93% are infected with G4. 6 10 The cause of these high seroprevalence rates are likely multifactorial; however, the widespread use of parenteral antihelminthics to combat schistosomiasis is believed to be predominately responsible for the scale of the epidemic. In 55–59 year olds (a population that is likely to have a higher burden of fibrosis due to the length of infection), the prevalence rate approaches 40%.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent study that screened 6600 participants aged between 17 and 58 years of age found 1018 (15.42%) participants positive for HCV, and among these, 62.4% had evidence of liver cirrhosis. 10 Other estimates put the numbers of compensated and decompensated cirrhotics in Egypt at 630 000 and 138 000, respectively. 11 Such a large burden of advanced disease puts a considerable strain on the already overstretched health resources of the country.…”
Section: Introductionmentioning
confidence: 99%
“…For our knowledge there is no study have used data mining analysis of such big data related ACS and Pylori, that artificial intelligence of Rapid I used in the current study can find the accurate or possible situation associations, hence according to our results only ACS of long duration of intermittent typical chest pain may becaused by Pylori chronic infection [8][9][10][11][12][13][14][15][16][17][18][19][20]. Data mining is the breakthrough in economy, biology, trading, business, astronomy and medicine [21][22][23]. Data mining can predict disease related-mortality and morbidity that will influence the overall medical progress [24][25][26].…”
Section: Methodsmentioning
confidence: 99%